2010
DOI: 10.1111/j.1365-2133.2010.09874.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features of 20 Japanese patients with vascular-type Ehlers-Danlos syndrome

Abstract: The analysis in the present series revealed a low frequency of patients presenting with serious clinical findings such as arterial rupture/arterial dissection/aneurysm and perforation or rupture of the gastrointestinal tract, and revealed a higher prevalence of splice-site mutations at the junction of the triple-helical exons than of glycine substitution mutations in COL3A1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Here, again some mutations (mostly splice site mutations) are likely to cause mRNA instability and nonsense‐mediated decay, while others (glycine substitutions) presumably hinder the folding of three collagen α1(III) chains into a triple helix (42,43). Interestingly, a recent study showed that both splice site and glycine substitution mutations resulted in a drastic reduction in the amount of collagen III at the protein level (44), supporting the notion that misfolded collagen trimers fail to pass the quality control in the endoplasmic reticulum and consequently are targeted for degradation (8,15). The outcome of both scenarios is that reduced amounts of an otherwise structurally normal collagen III are insufficient to form functionally correct collagen fibrils (Fig.…”
Section: Extracellular Matrix Dysfunction and Cutaneous Diseasesmentioning
confidence: 85%
“…Here, again some mutations (mostly splice site mutations) are likely to cause mRNA instability and nonsense‐mediated decay, while others (glycine substitutions) presumably hinder the folding of three collagen α1(III) chains into a triple helix (42,43). Interestingly, a recent study showed that both splice site and glycine substitution mutations resulted in a drastic reduction in the amount of collagen III at the protein level (44), supporting the notion that misfolded collagen trimers fail to pass the quality control in the endoplasmic reticulum and consequently are targeted for degradation (8,15). The outcome of both scenarios is that reduced amounts of an otherwise structurally normal collagen III are insufficient to form functionally correct collagen fibrils (Fig.…”
Section: Extracellular Matrix Dysfunction and Cutaneous Diseasesmentioning
confidence: 85%
“…Three identical pro-a1(III) chains, consisting of a central collagenous domain with repeated [Gly-X-Y] 343 triplets and two flanking amino-and carboxy-terminal noncollagenous domains, are assembled into type III pro-collagen homotrimers. Approximately 200 mutations in the COL3A1 gene have been reported; the majority of these are missense mutations that substitute a glycine (68%), while 22% affect splice sites [3,4,7,8]. Approximately 200 mutations in the COL3A1 gene have been reported; the majority of these are missense mutations that substitute a glycine (68%), while 22% affect splice sites [3,4,7,8].…”
mentioning
confidence: 99%
“…92 Furthermore, there are spontaneous de novo mutations without a family history making a correct diagnosis even more difficult. There may also be racial differences.…”
Section: Discussionmentioning
confidence: 99%